2016
DOI: 10.1371/journal.pone.0164287
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interspecific Interactions as Proximate Determinants of Sexual Dimorphism and Allometric Trajectories in the Bottlenose Dolphin Tursiops truncatus (Cetacea, Odontoceti, Delphinidae)

Abstract: Feeding adaptation, social behaviour, and interspecific interactions related to sexual dimorphism and allometric growth are particularly challenging to be investigated in the high sexual monomorphic Delphinidae. We used geometric morphometrics to extensively explore sexual dimorphism and ontogenetic allometry of different projections of the skull and the mandible of the bottlenose dolphin Tursiops truncatus. Two-dimensional landmarks were recorded on the dorsal, ventral, lateral, and occipital views of the sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
3
3
0
Order By: Relevance
“…Pillai trace, Wilks’ lambda, Hotelling's T 2 , and Roy's greatest root) were concordant in returning a highly significant effect of area ( P < 0.0001 for all tests), no significant effects of sex ( P > 0.5 for all tests), and a significant effect of area and sex interaction ( P ranging between 0.014 and 0.020). These outcomes suggest the likely existence of SShD in selected populations (Cheng & Kuntner, 2015), similar to recent findings in T. truncatus (De Francesco & Loy, 2016).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Pillai trace, Wilks’ lambda, Hotelling's T 2 , and Roy's greatest root) were concordant in returning a highly significant effect of area ( P < 0.0001 for all tests), no significant effects of sex ( P > 0.5 for all tests), and a significant effect of area and sex interaction ( P ranging between 0.014 and 0.020). These outcomes suggest the likely existence of SShD in selected populations (Cheng & Kuntner, 2015), similar to recent findings in T. truncatus (De Francesco & Loy, 2016).…”
Section: Resultssupporting
confidence: 89%
“…Although dolphins are characterized by a general absence of sexual dimorphism (Ralls, 1977;Ralls & Mesnick, 2002), the results obtained on common dolphins confirm the existence of SSD, with males larger than females, as observed by and Perrin (1984). Additionally, the results of MANOVA on shape coordinates indicated a significant interaction between marine area and sex, suggesting the possible occurrence of SShD in selected populations (Cheng & Kuntner, 2015), similar to the recent findings in T. truncatus showing SShD in populations living in monospecific associations (De Francesco & Loy, 2016). These results deserve further investigation in terms of the role of size and shape in sexual dimorphism in the common dolphin.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Aviki et al [ 17 ] focused on oncological care, and their review indicated positive effects but did not provide sufficient evidence. For example, one of the studies [ 34 ] showed an increase in guideline adherence but only for two of the five types of cancer analyzed. Another study [ 35 ] discovered a reduction in hospitalization and radiotherapy, but the cost of chemotherapy drugs increased.…”
Section: Resultsmentioning
confidence: 99%